I’dadu Mawad Ta’lim al-Lughah al-‘Arabiyyah li al-Dirasah al-Idhafiyah ‘ala al-Mustawa al-Jami’i li Tanmiyah al-Maharaat al-Lughawiyah: Dirasah Halah fi Ma’had Namira al-‘Ali Lamongan - Ahmad Afandi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The book used in the teaching activities at the Nimrah Higher Institute of Lamongan is the Arabic “بين يديك سلسلة في تعليم اللغة العربيىة لغير الناطقين بها